Hubungan antara Rasio Neutrofil Terhadap Limfosit Preterapi dengan Angka Harapan Hidup Pasien Karsinoma Nasofaring di RSUD Abdoel Wahab Sjahranie Tahun 2018 - Aulia, Nabiella Hasti; Irawiraman, Hadi; Susanti, Eva (Faculty of Medicine, Universitas Andalas, 2023)
Nasopharyngeal carcinoma is a malignancy that originates from the epithelial tissues lining the nasopharynx and is considered one of the most common malignant cancers which cause mortality in Indonesia. Neutrophils and lymphocytes are the first lines to provide body immunity against foreign substances. Neutrophil-to-Lymphocyte Ratio (NLR) is a prognostic factor in various malignancies. Objective: To investigated the correlation between pre-therapy Neutrophil-to-Lymphocyte Ratio (NLR) and survival rate among patients with nasopharyngeal carcinoma at Abdoel Wahab Sjahranie Regional Public Hospital in 2018. Methods: The Neutrophil-to-Lymphocyte Ratio (NLR) data were obtained from outpatient medical records at Abdoel Wahab Sjahranie Regional Public Hospital in 2018. In addition, the data on mortality status were collected based on the information after directly contacting the patients. A purposive sampling technique was used to collect the data. Thirty-three data of patient medical records were obtained and analyzed using Kaplan-Meier survival analysis with a significant p-value of <0.05. Results: The analysis result showed p-value of 0.495. Conclusion: There is no correlation between pre-therapy Neutrophil-to-Lymphocyte Ratio (NLR) and survival rate among patients with nasopharyngeal carcinoma.Keywords: Â nasopharyngeal carcinoma, neutrophil-to-lymphocyte ratio, survival rate